Sites in the Poetry of Northern Ireland and the Postcolonial Debate - Grgas, Stipe (1999)
The article attempts to make a contribution to the postcolonial debate concerning Ireland, asking the questin whether Ireland can be considered a postcolonial site. The author offers the factor of the sense of place as a measuring rod for a positive answer.
ENG